ETHICAL PROBLEM-SOLVING EXPECTATIONS AND ECO-TOUR COMPANY OPERATIONAL ISSUES: VIEWS OF POTENTIAL EMPLOYEES - GLENN F. ROSS (Centre For Tourism Planning and Development, 2005)
Many travelers now reveal a growing interest in eco-tourism, with the tourism industry in the Asia-Pacific region showing an increase in the number and diversity of eco-tour operators. Relatively little, however, is known about the various ethical beliefs and ethical problemsolving response styles that potential employees bring to such a work context. This study has examined both competence and integrity ethical values, ethical influences and problem-solving responses in regard to an eco-tourism work place dilemma involving unethical operating procedures, leading to pollution of the environment. University business students from a major Australian tourist destination reported that competence ethical values to be important. Tourists were expected to rate integrity ethical values highly, as did respondents who rated tourists' integrity ethical values more highly than tourists' competency ethical values. Organizational mistrust was found to be a widespread expectation among many respondents. The implications of this research for university ethics education, for eco-tourism operations management and for future research within this domain are examined.